Top Views and Technologies for Measuring Territories (diségno, 2023)
The man has always nurtured the need to explore and represent the territory that surrounds him in order to know its qualities (including the extent) and, where it is possible, share the collected data. Over the centuries both the techniques and the methods of acquisition and restitution of information have changed, and that is extremely evident from the correlation between the different modes of representation of the graphic elaborations and the periods in which they were produced, so much so that chronological analysis makes the following reflection self-evident: the purpose for which these works were made changed according to culture and society. [read more]